First Records of the Guest Ant Formicoxenus Quebecensis Francoeur From Western Canada (Hymenoptera, Formicidae) - A. Buschinger; R. D. Schumann; J. Heinze (Psyche: A Journal of Entomology)
Formicoxenus quebecensis, a rare guest ant associated with Myrmica alaskensis as yet had been found only in southern Québec. Here we report on five new localities in Alberta and British Columbia. The particular features of F. quebecensis, queen and male polymorphism, correspond in both areas.